Ectopic expression of Jatropha curcas JcTAW1 improves the vegetative growth, yield, and drought resistance of tobacco - Qingyan Peng; Chang Liu; Zhurong Zou; Mengru Zhang (BMC Plant Biology, 2023)
Abstract Background Jatropha curcas is a promising alternative bio-energy resource. However, underrun limited its broad application in the industry. Luckily, TAW1 is a high-productivity promoting gene that increases the lateral branches by prolonging the identification of inflorescence meristems to generate more spikes and flowers. Results In the current study, we introduced the Jatropha JcTAW1 gene into tobacco to depict its functional profile. Ectopically expressed JcTAW1 increased the lateral branches and ultimate yield of the transgenic tobacco plants. Moreover, the JcTAW1 lines had significantly higher plant height, longer roots, and better drought resistance than those of wild-type (W.T.). We performed RNA sequencing and weighted gene co-expression network analysis to determine which biological processes were affected by JcTAW1. The results showed that biological processes such as carbon metabolism, cell wall biosynthesis, and ionization transport were extensively promoted by the ectopic expression of JcTAW1. Seven hub genes were identified. Therein, two up-regulated genes affect glucose metabolism and cell wall biosynthesis, five down-regulated genes are involved in DNA repair and negative regulation of TOR (target-of-rapamycin) signaling which was identified as a central regulator to promote cell proliferation and growth. Conclusions Our study verified a new promising candidate for Jatropha productive breeding and discovered several new features of JcTAW1. Except for boosting flowering, JcTAW1 was found to promote stem and root growth. Additionally, transcriptome analysis indicated that JcTAW1 might promote glucose metabolism while suppressing the DNA repair system.